Oleoresin Kayu Manis (Cinnamomun Burmannii) Dengan Metode Ekstraksi Sokhletasi (Mempelajari Pengaruh Waktu Ekstraksi Dan Volume Pelarut) - Ani Melani; Mardwita Mardwita; Robiah Robiah; Jannatul Fitri (LPPM Politeknik Jambi, 2026)
Cinnamon is a spice product that is often found in Indonesia. Indonesia still exports it in the form of cinnamon rolls (quill) which have low economic value when compared to essential oils or oleoresin, consequently the welfare of farmers is still low. In this research, the production of cinnamon oleoresin was conducted by the Sokhlet Extraction method. The sample used was cinnamon powder with a size of 100 mesh with a weight of 20 gr, then the volume variation of the solvent (ethanol 96%) (80; 120; 160; 200; 240) ml and extraction times were 3; 3.5; 4; 4.5; and 5 hr at 80 °C. The extraction results are then distilled, to separate the solvent (ethanol) with oleoresin at a temperature of 80 °C. This study was conducted to determine the effect of solvent volume variation and extraction time on the production of cinnamon oleoresin, the percentage of yield, sinamaldehyde content and density. The results showed the highest pecentage was obtained at solvent volume (ethanol 96%) 200 ml, with 4.5 hr with a percentage of rendement 63,73%, levels of cinamaldehyde 74% and density of 1.0054 gr/l, these meets the quality standard of cinnamon bark oil (SNI 06-3734-2006).